Social Entrepreneurship in Russia: Key Actors and the Development Potential - Алена Игоревна Албутова (Journal of Economic Sociology, 2013)
In the article, the different approaches to defining social entrepreneurship are presented as well as the results of research dedicated to the emerging organisational field of social entrepreneurship in Russia. While this type of economic activity is institutionally constituted in the US and Western Europe, where there are specific laws and tax privileges, in Russia it has just only started to develop. Its manner of development in Russia depends not only on social and economic factors and historic conditions but on the activities of key players in this emerging field. The expert interviews conducted at the first stage of the research helped the author to distinguish those key players, including the «Our Future» fund, which served as a single source of financial support for social entrepreneurship as the research was conducted: 186 applications submitted to competitions for social entrepreneurs held by the fund over three years are analysed to discover the model of social entrepreneurship promoted by the fund. According to the results, the stability and financial independency of social projects are referred to the key characteristics of social projects supported by the fund.